TINGKAT KESEGARAN JASMANI SISWA SMA NEGERI 10 BONE TERHADAP KEMAMPUAN SMASH DALAM PERMAINAN BOLA VOLI - Ahmad Rehza Adrianto; Abdul Rahman; Sulaeman Sulaeman (Program Studi Ilmu Keolahragaan FIK UNM, 2023)
The purpose of this study was to analyze the level of physical freshness of the students of SMA Negeri 10 Bone on the Smash Ability in the Volleyball Game. This research is a quantitative descriptive study, which intends to describe or provide an overview of the Physical Freshness Level of Students at SMA Negeri 10 Bone on Smash Ability in Volleyball Game. The population in this study were women's volleyball players at SMA Negeri 10 Bone and the sample of this study used the Total Sampling technique. The data analysis technique in this study used a descriptive test, and a percentage test. The results of the research on physical fitness in Bone State Senior High School students, namely 10 respondents, obtained a minimum score of = 34.23, maximum score = 57.86, SUM = 451.88, range = 23.63, average = 50.20 and Physical Fitness test results to measure the ability of State Senior High School students Bone obtained the value of N (Sample) = 10, minimum = 7, maximum = 13, sum = 104, mean = 10.4 Based on data analysis, it can be concluded that the Physical Fitness Level of 10 Bone State Senior High School students, where the 60 meter running test, vertical Jump, Sit Up, Pull Up obtained 60% in the Medium category. And the Smash Ability Test of SMA Negeri 10 Bone students, obtained 90% in the Medium category